Architecting Prosperity: Public Procurement as the Foundational Blueprint for Ghana’s Digital, Green, and Self-Sufficient Economic Future (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Ghana's annual public procurement expenditure of $3.5 billion, accounting for 11% of GDP, serves as a significant but underleveraged framework for addressing the country's interconnected issues of digital exclusion, climate vulnerability, and import dependency. This research goes beyond traditional administrative perspectives, introducing a transformative "Procurement 4.0" framework aimed at strategically harnessing fiscal power. The framework integrates artificial intelligence, blockchain, and multi-stakeholder governance to align procurement with three key imperatives: facilitating digital leapfrogging through AI-driven tender platforms that enhance SME access, catalyzing green industrialization with mandatory sustainability criteria and life-cycle assessments, and promoting SME-driven self-sufficiency via enforceable participation quotas and capability development. The study utilizes policy archaeology (2010-2024), multi-criteria scenario modeling, and stakeholder gap analysis to illustrate that recalibrating strategic procurement can enhance SME contributions to GDP from 17% to 25%, attain 40% green procurement compliance by 2035, and achieve notable AI-driven efficiency savings. The findings provide a clear and practical framework for Ghana and comparable Global South economies aiming to transform public spending into drivers of technological sovereignty, climate resilience, and inclusive structural change, fundamentally reshaping the role of procurement in fostering prosperity.